An Analysis Of Language Features Used By English Language Education (ELE) Students Through WhatsApp Group - Ni Komang Suciati; Dewa Putu Ramendra; Dewa Ayu Eka Agustini (Jurnal Penelitian Mahasiswa Indonesia, 2022)
A language is an important tool used by men and women in communicating with many people in society. Many factors influence the way people communicate or how they use languages, such as geography, age, social status, gender, etc. A factor that can create language variation is gender. One of the language variations caused by social factors such as gender gives rise to a term called language features. This study focuses on analyzing the language features used by English Language Education students through WhatsApp Group. The purpose of this research was to answer what types of language features are used by men and women English Language Education students through WhatsApp Group. The design of this research was the descriptive qualitative method. In this study, the researchers used two instruments an observation sheet and an interview. The data were analyzed by identifying and classifying the ten types of language features proposed by Lakoff (1975). The findings showed that there were only five features that have been classified as language features used by English Language Education students on WhatsApp group. Those are lexical hedges, tag questions, rising intonation, intensifiers, and super polite forms. Each features has a function in communication.